CHARACTERISTICS OF PATHOMORPHOLOGICAL CHANGES IN LYMPHOCYTIC LEUKOSIS IN CHILDREN - Ibadullayeva S.S; Yakubov K.Y; Artikov I.A; Nurllayev R.R; Sadullayev S.E. (Western European Studies, 2023)
Lymphoid leukosis is a malignant disease in which the bone marrow produces a large number of immature, unable to perform their functions of lymphocytes. Lymphocytes are a type of white blood cells and are responsible for immunity. Malignant leukocytes do not cope with the protective function, while they suppress the formation of normal blood cells and disrupt the functioning of other organs. The main purpose of the article is to identify specific pathomorphological changes in lymphocytic leukemia in young children. Pediatric lymphocytic leukemia is pathomorphologically manifested by focal leukemic infiltration in the bone marrow and in almost all lymphoid organs at the onset of the disease. Lymphocytic leukemia is characterized by the appearance of leukemic infiltration in specific areas of the lymphoid organs, depending on whether it develops from T or B lymphocytes. In lymphocytic leukemia, pathomorphological changes first appear in the stroma-vascular structures of the organs and then spread to the parenchyma.
Keywords: leukosis; lymphoid leukosis; bone marrow